ANALISIS ABNORMAL RETURN SAHAM SEBELUM DAN SESUDAH PENGUMUMAN PERATURAN LOAN TO VALUE KPR (Studi Pada Perusahaan Properti Di Bursa Efek Indonesia) - Dwi Suharyanto; Rusdayanti Asma (Universitas Lambung Mangkurat, 2013)
This study aims to analyze the abnormal stock return of property companies in Indonesia Stock Exchange as a result of the announcement of Bank Indonesia on the restriction of the maximum Loan to Value (LTV) of the mortgage loans. This study uses event study, which observed the average abnormal return over the 10 days prior to the announcement up to 10 days thereafter. The results showed that there was no significant difference between the abnormal returns before and after the announcement. However, there is an increase in the number of days that experienced abnormal returns, ie 2 (two) days in the period before the announcement of a 5 (five) days in the period thereafter. While at the moment of announcement there is no abnormal return. This suggests that the effect of the announcement was not immediately responded by the market, but there is a lag time for the market to react. These conditions may be caused investors do not have the experience to identify and measure the impact of LTV mortgage regulation. Significant abnormal return occurs also varies, which is experiencing abnormal gain 3 days and 4 days of having abnormal loss, which shows the confusion in the market so it happened a few times stock price correction. Another possibility for the market considers these policies also have a positive side. Properties company performance may be declining, but the industry would likely have a positive impact in the long run because it will reduce the risk of price bubbles.